Ocean-rafted pumice constrains postglacial relative sea-level and supports Holocene ice cap survival - Farnsworth, Wesley Randall; Blake Jr., Wesley; Gudmundsdottir, Esther Ruth; Ingólfsson, Ólafur; Larsen, Gudrún; Óladóttir, Bergrún Arna; Schomacker, Anders (Quaternary Science Reviews, 2020)
Distally deposited tephra from explosive volcanic eruptions can be a powerful tool for precise dating and correlation of sedimentary archives and landforms. However, the morphostratigraphic and chronological potential of ocean-rafted pumice has been under-utilized considering its long observational history and widespread distribution on modern and palaeo-shorelines around the world. Here we analyze the geochemical composition and elevation data of 60 samples of ocean-rafted pumice collected since 1958 from raised beaches on Svalbard. Comparison of pumice data with postglacial relative sea-level history suggests eight distinct pumice rafting events throughout the North Atlantic during the Middle and Late Holocene. Analyzed ocean-rafted pumice exhibit consistent silicic composition characteristic of deposits from Iceland’s volcanic system, Katla. Eruption-triggered jökulhlaups are key drivers of the transport of pumice from the Katla caldera to beyond the coast of Iceland and into the surface currents of the North Atlantic Ocean. Thus, the correlation of distinct, high-concentration pumice horizons from Katla deposited along raised Middle Holocene beach ridges in Svalbard further advocates for the persistence of the Mýrdalsjökull ice cap through the Holocene thermal maximum.